Dublin's north fringe: a new model for suburban greenfield development - Gleeson, Dick (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
The process described here represents a negotiated Masterplan initiated by Dublin Corporation to provide a coherent urban design and implementation framework for the development of a major new urban area on the northern fringe of the city. This approach was adopted in order to comply with policy requirements regarding more sustainable mixed use urban development patterns. Specific issues addressed in the proposal include the inclusion of a wide range of uses, the distinct character of different areas , the provision of an infrastructural 'spine', amenity areas and public parks. The area covered by this initiative includes lands owned by Dublin Corporation and a number of private owners. Applications for planning permission are currently being formulated based upon the agreed framework. Development permission will be granted to applications that include the required mix of private, affordable and social housing in compliance with the planning Acts, and such development will have to comply with the permissions and conditions as granted.
Papers from practice
Keywords: Urban geography -- Ireland